2004
DOI: 10.1210/en.2004-0515
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Targeting of Relaxin and Insulin-Like Factor 3 Receptors in Mice

Abstract: Relaxin (RLN) is a small peptide hormone that affects a variety of biological processes. Rln1 knockout mice exhibit abnormal nipple development, prolonged parturition, agerelated pulmonary fibrosis, and abnormalities in the testes and prostate. We describe here RLN receptor Lgr7-deficient mice. Mutant females have grossly underdeveloped nipples and are unable to feed their progeny. Some Lgr7-/- females were unable to deliver their pups. Histological analysis of Lgr7 mutant lung tissues demonstrates increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(154 citation statements)
references
References 29 publications
3
148
1
Order By: Relevance
“…The closely related insulin-like 3 peptide receptor RXFP2 also responds to higher doses of RLN by cAMP increase in cells transfected with RXFP2 (Feng et al 2007), however, such crossreactivity was not detected in vivo (Kamat et al 2004. Despite significant variations in the amino acid sequence of different mammalian RLN peptides, they all efficiently cross-activate human RXFP1 (Sherwood 2004, Bathgate et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…The closely related insulin-like 3 peptide receptor RXFP2 also responds to higher doses of RLN by cAMP increase in cells transfected with RXFP2 (Feng et al 2007), however, such crossreactivity was not detected in vivo (Kamat et al 2004. Despite significant variations in the amino acid sequence of different mammalian RLN peptides, they all efficiently cross-activate human RXFP1 (Sherwood 2004, Bathgate et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…13 The differences in thyroidal expression pattern between relaxin and INSL3 implicate distinct functional roles for each of the relaxin-like members in the human thyroid and evidence in mice suggests that relaxin and INSL3 appear to activate distinct LGR7-and LGR8-mediated signaling pathways, respectively. 26 Stable transfectants of the relaxin-responsive human follicular thyroid carcinoma cell lines FTC-133 and FTC-238 were used to analyze functional roles of RLN2 in human neoplastic thyrocytes. These transfectants produced a single proRLN2 immunoprotein indicating incomplete processing of RLN2 hormone in these thyroid carcinoma cells likely reflecting their limited capacity to process constitutively produced relaxin proform.…”
Section: Discussionmentioning
confidence: 99%
“…Relaxin (RLN) was initially described as a hormone of pregnancy that is best known for its role during parturition in various species, but it has also been implicated in regulation of testicular function, although testicular source of the hormone in mammalian males still remains largely unknown (Sherwood 1994, 2004, Kohsaka et al 2003. Recent studies in adult male mice with knockout of the gene encoding either RLN or its distinct receptor, now known to be RLN family peptide receptor 1 (RXFP1; originally called LGR7, leucine-rich repeat-containing G-protein-coupled receptor 7) (Hsu et al 2002), have demonstrated a decrease in sperm maturation, an increase of apoptosis in the testis and a reduction in the fertility of such mice (Samuel et al 2003, Krajnc-Franken et al 2004, although another study indicated normal male fertility in Rxfp1 knockout mice (Kamat et al 2004). …”
Section: Introductionmentioning
confidence: 99%